Analisis Materi Ajar Kimia SMA/MA Kelas X Pada Konsep Stoikiometri - Siti Fatimah Indah Sari; Abdul Hadjranul Fatah; Maya Erliza Anggraeni (FKIP Universitas Palangka Raya, 2020)
This study aims to analyze the teaching material in high school chemistry textbooks. The instruments used are micro-macro proposition identification tables, discourse macro structure models, and identification table propositions that have the potential for misconceptions (misconceptions). The data obtained were analyzed descriptively. The results showed that the concept labels analyzed totaling 46 concept labels, the concept labels in textbook A and text book B that corresponded to the 2013 curriculum syllabus were 34 and 37 respectively. The concept labels found only in book A totaled 9 and all of them according to the 2013 curriculum syllabus, and the concept labels that are only found in book B, number 12 and all are in accordance with the 2013 Curriculum Syllabus. the concept at level 2 as the scope of discussion, in the text book B the material presentation on the elaboration dimension reaches level 4, and the progression dimension at level 2 there are 8 concepts.